Imiquimod as an alternative to surgery in the treatment of skin cancers – experience with the first group of patients - Murawa, Dawid; Połom, Karol; Murawa, Paweł (Contemporary Oncology/Współczesna Onkologia, 2011)
Skin cancer is the most frequently occurring neoplasm in the world. In the last several decades its increasing occurrence has been observed. The basic method of treatment of skin cancers is surgical resection of the lesion. There are numerous alternative methods to resection of the lesion, such as cryosurgery, radiotherapy, photodynamic therapy, or pharmacological preparations (5-fluorouracil, 5% imiquimod – Aldara). Imiquimod is one of the more recent forms of treatment of skin cancers. Its mechanism is not fully known, though above all the activation of the immune system is postulated. This study presents a group of 4 patients who were offered treatment with imiquimod preparation as an alternative to surgical resection of the lesion. Complete regression of the lesions was observed in all of the patients and during the 12-26 months of observation no relapse of the neoplastic disease was noted. No significant adverse reactions were observed during treatment. It seems that the chief field of application of imiquimod may be skin lesions in locations difficult for surgical dressing, extensive wounds and in a group of elderly patients with numerous concomitant diseases, where all the treatment can be carried out at home.